Analytical Method Development and Validation for the Simultaneous Estimation of Buprenorphine Hydrochloride and Naloxone Hydrochloride in Pharmaceutical Dosage Forms By RP-HPLC - Damodar, Katasani (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT A simple, selective, linear, precise and accurate RP-HPLC method was developed and validated for the simultaneous estimation of Buprenorphine hydrochloride and Naloxone hydrochloride in pharmaceutical dosage forms. Isocratic elution at a flow rate of 1ml min-1 was employed on a symmetry C18 column at ambient temperature. The mobile phase consisted of Water:Methanol:0.1% Ortho phosphoric acid 60:20:20(v/v/v). The UV detection wavelength was at 273 nm. The retention time for Buprenorphine hydrochloride was 3.85 min and Naloxone hydrochloride was 5.85. The method was validated as per the ICH guidelines. The proposed method can be successfully applied for the estimation of Buprenorphine hydrochloride and Naloxone hydrochloride in pharmaceutical dosage forms.